Bibliometric mapping of microbiology research topics - Dehdarirad, Tahereh; Sotudeh, Hajar; Freer, Jonathan (FEMS microbiology letters, 2019)
Amongst health-related scientific disciplines, microbiology appears to play a vital role in creating a sustainable future with respect to health, the environment and a biobased economy. Microbiology research covers a wide range of different disciplines and addresses many important global issues. This study aimed to identify topics being addressed within the last 5 years (2012-16) in the field of microbiology worldwide and to compare them in terms of three different indicators: gross domestic product, Human Development Index and Infectious Disease Vulnerability Index. The dataset of this study comprised 167 874 articles and reviews from 2012 to 2016, which were extracted from the Web of Science Medline. To identify and visualise the topics addressed during the studied period, VOSviewer was used. The construction and visualisation of the term map was done based on 5918 MESH subject headings. The methodology and procedures employed included Kruskal-Wallis test and two-sample proportion test. Overall, our study showed that the field of microbiology has focused on six different topics during 2012-16. The papers written with the collaboration of countries with low socioeconomic status and high vulnerability to infectious diseases mainly addressed topics related to the primary needs of people such as food safety, the prevention and control of infectious diseases, food and energy poverty. In contrast, papers written with the collaboration of countries with high socioeconomic development status and less vulnerability to infectious diseases mainly focused on big data, alternative methods to animal experiments.